In vitro antifungal activity of allicin alone and in combination with two medications against six dermatophytic fungi - Aala, Farzad; Yusuf, Umi Kalsom; Khodavandi, Alireza; Jamal, Farida Fatema @ Farida (Academic Journals, 2010)
Dermatophytes are fungi capable of invading keratinized tissues of humans and animals, causingdermatomycosis. Azole antifungal drugs are often used in the treatment of dermatomycosis. Because ofincreased use of these medications, azoles are known to cause drug resistance; hence this studyinvestigated an alternative anti-dermatophyte which is plant-based, and biodegradable natural product.Allicin is a pure bioactive compound derived from garlic, which is known worldwide for its antifungalactivities. This study evaluated thein vitro efficacy of pure allicin alone against six dermatophyteisolates and the MIC50 and MIC90 ranged from 0.098 – 25.0 µg/ml. Results of this study showed that theorder of efficacy based on the MICs values was fluconazole > allicin > ketoconazole at 28ºC for both 7and 10 days incubation. On the other side, most of tested drug combinations demonstrated synergisticor additive interaction for all isolates for both 7 and 10 days incubation at 28ºC. In conclusion allicinalone showed very good potential as an antifungal compound against mycoses-causingdermatophytes, performing better than the synthetic drug fluconazole, and almost the same asketoconazole, furthermore allicin in combination with ketoconazole or with fluconazole frequentlyshowed synergistic or additive interaction against dermatomycosis.